Forecasting the influence of vehicle columns with liquid cargoes on bearing systems in agriculture - Gridnev Sergey; Budkovoy Alexey; Skalko Yuriy; Muchtarov Rinat (E3S Web of Conferences, 2020)
Studies have been performed to evaluate the dynamic effect of columns of the same type of agricultural tanker truck on the beam-bearing systems of transport structures during movement in braking mode. The design scheme of the general oscillatory system is selected, a mathematical and numerical model of its behavior is developed, an algorithm for joint nonlinear oscillations is constructed. On the basis of the developed expert models, a computer complex was created using the simulation package of dynamic and event-driven systems Simulink MATLAB systems. Using it, a series of computational experiments was carried out to simulate situations of passage of convoys of cars with different parameters and with different driving modes. Various parameters varied: the speed of the column, the distance between the cars, the speed at the time of the start of braking, the place where the first car began to brake, the amount of steady deceleration, the number of tank compartments, and the value of operational underfilling. Based on the analysis of the results of numerical studies, the features of the dynamic effect of vehicles convoys carrying liquid cargo on load-bearing systems from the standpoint of the emergence of excess dynamic pressure on transport facilities and the need for its consideration are shown. Cases of a dangerous combination of parameters and driving modes are highlighted, and the need to distinguish such columns in a special class of moving load is shown. A significant increase in the dynamic coefficients of deflections in comparison with solid loads is shown. The need for full-scale research in this area with the aim of introducing amendments to regulatory documents has been proved.